Clinical Evaluation of MyoCare in Europe (CEME): study protocol for a prospective, multicenter, randomized, double-blinded, and controlled clinical trial - Cristina Alvarez-Peregrina; Miguel Angel Sanchez-Tena; Clara Martinez-Perez; Cesar Villa-Collar; Clinical Evaluation of MyoCare in Europe –the CEME Study Group; Arne Ohlendorf (Trials, 2023)
Abstract Background Myopia prevalence has been increasing in the last decades, and its pathological consequences, including myopic maculopathy and high myopia-associated optic neuropathy, are now one of the most common causes of visual impairment. It is estimated that by 2050, more than 50% of Europeans and Americans will be myopes, which is alarming due to the high morbidity of myopes over − 6.00D. Once myopia has appeared, there are different options with scientific evidence to try to slow the axial length growth. Ophthalmic lenses are the less invasive treatment to control myopia, and there is evidence about the efficacy of different designs, mainly in the Asiatic population. However, new designs have been launched, and it is not known if efficacy is the same between Asiatic and European subjects. Thus, we have set up a randomized, controlled, double-blind, and multicenter trial to investigate the efficacy of a new design of ophthalmic lenses for myopia control in European children. Methods A 2-year prospective, multicenter, randomized controlled, and double-blind clinical trial is used to investigate the efficacy of a new design of ophthalmic lenses to slow the progression of myopia. Three hundred children aged from 6 to 13 years old will be recruited and randomly assigned to a study or control group. The study group will be composed of 150 children wearing MyoCare while the control group will be composed of 150 children wearing Clearview. The inclusion criteria will be myopia with a spherical equivalent between − 0.75D and − 5.00D, astigmatism < 1.50D, and anisometropia < 1.00D and having a historical evolution of at least − 0.50 The primary outcome is to compare the mean annual progression of the spherical equivalent between both groups. The secondary outcomes are axial length, choroidal thickness, phorias, and accommodative status of both groups. Discussion This study will be the first randomized and controlled clinical trial in European children with spectacle lenses based on simultaneous competing defocus. The results will shed light on the clinical evidence of spectacle lenses relying on this new design for the management of myopia with results of efficacy in the non-Asiatic population. Trial registration EU Clinical Trials Register (EudraCT) 2022–001696. Registered on 27 April 2022. ClinicalTrials.gov NCT05919654. Registered on 26 June 2023.